Daclizumab high-yield process in relapsing-remitting multiple sclerosis (SELECTION): a multicentre, randomised, double-blind extension trial - Giovannoni, Gavin; Gold, Ralf; Selmaj, Krzysztof; Havrdova, Eva; Montalban, Xavier; Radue, Ernst-Wilhelm; Stefoski, Dusan; McNeill, Manjit; Amaravadi, Lakshmi; Sweetser, Marianne; Elkins, Jacob; O'Neill, Gilmore (Lancet neurology, 2014)
BACKGROUND: In the SELECT trial, disease activity was reduced in patients with multiple sclerosis who received daclizumab high-yield process (HYP) for 52 weeks. The primary aim of the SELECTION extension study was to assess the safety and immunogenicity of extended treatment with daclizumab HYP. METHODS: A multicentre, randomised, double-blind, 52-week extension trial was done in 74 centres in the Czech Republic, Germany, Hungary, India, Poland, Russia, Ukraine, and the UK between Feb 13, 2009, and Oct 3, 2012. Eligible patients were aged 18-55 years, had relapsing-remitting multiple sclerosis, and had completed the SELECT study. Patients who received placebo in SELECT were randomly assigned (1:1) to receive 150 mg or 300 mg subcutaneous daclizumab HYP every 4 weeks for 52 weeks (treatment initiation group); those who had received daclizumab HYP were randomly assigned (1:1) to continue their present dose with (washout and re-initiation group) or without (continuous treatment group) a washout period of 20 weeks. All randomisation was done with a centralised, interactive voice-response system. Patients and personnel were masked to treatment assignment, except for the site pharmacist who prepared the study drug but had no interaction with patients. The primary endpoints were the safety and immunogenicity of daclizumab HYP. Analyses were by intention to treat. This study is registered with ClinicalTrials.gov, number NCT00870740. FINDINGS: 517 (91%) of 567 patients who completed the SELECT trial entered SELECTION, of whom 170 were in the treatment initiation group, 173 in the continuous treatment group, and 174 in the washout and re-initiation group. 11 patients in the treatment initiation group (6%), 13 in the continuous treatment group (8%), and ten in the washout and re-initiation group (6%) had any serious adverse event other than relapse of multiple sclerosis. One patient in the washout and re-initiation group (300 mg daclizumab HYP) died because of autoimmune hepatitis; a contributory role of daclizumab HYP could not be excluded. Seven patients tested positive for neutralising antidrug antibodies: one (1%) of 128 for whom data were available in the continuous treatment group (this patient also tested positive at SELECTION baseline), four (2%) in the treatment initiation group, and two (2%) of 129 in the washout and re-initiation group. INTERPRETATION: Adverse events and immunogenicity were not increased in the second year of continuous treatment with daclizumab HYP or during treatment washout and re-initiation. These results support further assessment of daclizumab HYP for relapsing-remitting multiple sclerosis. FUNDING: Biogen Idec and AbbVie Biotherapeutics.
Keywords: dospělí; Double-Blind Method; Immunoglobulin G; Kaplan-Meier Estimate; relabující-remitující roztroušená skleróza; imunosupresiva; Humans; Magnetic Resonance Imaging; následné studie; lidé středního věku; Middle Aged; Europe; Kaplanův-Meierův odhad; magnetická rezonanční tomografie; Time Factors; Follow-Up Studies; mužské pohlaví; humanizované monoklonální protilátky; Adult; Multiple Sclerosis, Relapsing-Remitting; Antibodies, Monoclonal, Humanized; výsledek terapie; Evropa; časové faktory; imunoglobulin G; Treatment Outcome; ženské pohlaví; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Immunosuppressive Agents; lidé; Male; dvojitá slepá metoda; Female